Ultrasonic–probe assisted extraction of phenolic acids in ionic liquid from quercus infectoria galls - Nuramira Fateha, Sukor (2019)
Quercus Infectoria (QI) galls or commonly known as Manjakani was widely used in folklore medicine due to its remarkable active ingredients of phenolic acids including gallic acid (GA) and tannic acid (TA). However, the extraction methods to extract the phenolic acids have several limitations related to high toxicity and low efficiency. In this study, the effect of the phenolic acids from QI galls extraction method and operating conditions were studied. The phenolic acids from QI galls were extracted via ultrasonic–probe assisted extraction (UPAE) method using ionic liquid solvent, conventional aqueous extraction (CAE) method, hydro–distillation extraction (HDE) method and classical ultrasonic–bath assisted extraction (CUBAE) method. The result indicate that the UPAE method yielded highest extraction amount of GA followed by CUBAE, CAE and HDE method at 130.76 mg/g, 81.56 mg/g, 43.76 mg/g and 14.74 mg/g, respectively. On the other hand, the extraction yield of TA was higher than the GA, having a same pattern with the highest value of extraction yield via UPAE, followed by the CUBAE, CAE and HDE method with 1556.26 mg/g, 810.74 mg/g, 179.97 mg/g and 118.02 mg/g, respectively. The UPAE method extraction yield exceededs the other conventional methods because it utilized acoustic cavitation to disrupt the plant tissues, broke down cell membrane and eventually decreased mass transfer limitations. The performance of the ionic liquids, namely 1-Butyl-3-methylimidazolium tetrafluoroborate, [Bmim][BF4] and 1-Butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [Bmim][Tf2N] as solvents were also compared with water, organic solvent and Cetyltrimethylammonium bromide (CTAB) surfactant. The results show that [Bmim][Tf2N] ionic liquid gave highest extraction yield which might due to the long alkyl chain of imidazolium cation and the complexity of the Tf2N anion, that might form strong hydrogen bond with the hydroxyl group of phenolic acids, extracted it out from the solid sample and eventually increased the efficiency of the extraction process. The operating conditions for the UPAE process were also investigated. It is found that the highest amount of GA (870.90 mg/g) and the TA (3157.97 mg/g) were achieved at 70oC with 40% duty cycle, sample dilution in solvent [Bmim][Tf2N] at concentration of 0.10 M with sample–to–solvent mass ratio of 1:10 for 8 hours. A high antioxidant activity of IC50, 26.57 μg/mL was obtained at the same condition. The characterization results of QI galls using FT–IR Spectrometry and SEM confirmed that high ultrasonic intensity from UPAE method was able to extract high amount of phenolic acids into the extraction media. Moreover, the RSM analysis for the UPAE method of the phenolic acids showed a good significance of model with low probability values (<0.0001) and a high coefficient of determination (R2). The optimum conditions for the extraction process were found to be at 9.14 hours, sample–to–solvent mass ratio of 1:6 and temperature at 75oC, attaining maximum phenolic acids of 4119.77 mg/g. By modeling via rate law, Peleg’s and Fick’s mathematical models, Fick’s model was successfully predicted the UPAE process with 97% accuracy compared to other kinetic models i.e. rate law model and Peleg’s model. This also confirmed that diffusivity factor controlled the extraction of phenolic acids from the QI galls using the ionic liquid. Significantly, the UPAE extraction process using ionic liquid as solvent could be a great advantage in the future development of extraction technology.